Improving Critical Thinking Skills in Thematic Learning with the Help of Problem Learning Models - Evi Damayanti; Reka Yuliyanti; Lukman Nulhakim; Mar’atun Najiah (Jurnal Penelitian Pendidikan IPA, 2023)
The low thinking ability of primary school students today is explained by the fact that teachers tend to use teaching models that are monotonous, boring and teacher-centered. Therefore, it is necessary to apply a model that will promote proper learning and stimulate the active role of students' critical thinking related to thematic learning. One of the correct models of learning is problem-based learning. Referring to this statement, the researcher is interested. Conduct a literature review to increase efforts. Critical thinking skills use a problem-based learning model. Thematic training. The results of this study indicate that the problem-based learning model can be effectively used in thematic educational activities. This model of problem-based learning can improve the process. By studying the nuances of life in the classroom, students will be activated and able to think critically and analytically improve students' thinking skills in thematic learning